Five Axioms of Things - Jianfeng Zhan (BenchCouncil Transactions on Benchmarks, Standards and Evaluations)
This article explicitly defines several concepts, such as variables, models, and truth of a thing, that are fundamental to natural and social sciences. I present a generalized methodology for understaning a thing, categorically defining six foundational understanding approaches based on the nature of the thing and diverse perspectives: conjecture, observation, experiment, evaluation, measurement, and testing. I extend my previous work on the five axioms of evaluation to understanding a thing, which I call the five axioms of things. Also, I comment on five paradigms of science.